Land Profit Sharing For Increasing Productivity - Ma'sumah, Siti; Luthfi Hamidi; Ibni Trisal Adam (Lafadz Jaya Publisher, 2023)
Indonesia is known for its rich agriculture, and rice is the staple food of the Indonesian people. The production of rice comes from rice fields, which are often managed by their owners or tenant farmers. However, not all rice field owners can efficiently manage their resources, which is why they can involve rice cultivators to help them out. The relationship between the owner of the rice fields and the tenant farmers is divided into two types of cooperation: maro and mertelu. Additionally, this type of cooperation can also be carried out in dry land areas, such as coconut plantations, coffee plantations, and more. This study focuses on the actors involved in maro and mertelu agreements in Banyumas Regency, Cilacap Regency, Kebumen Regency, Banjarnegara Regency, and Purbalingga Regency. The population size of this study is unknown, but based on calculations, a minimum sample size of 97 respondents is required. The criterion for selecting respondents is that they have entered into a maro or mertelu agreement and reside in one of the aforementioned regencies. The findings of the study indicate that individuals who have entered into maro or mertelu agreements do so for a variety of reasons. These reasons include supplementing their income to meet basic and other needs, ensuring they have a job and are not unemployed, and following the orders of the landowner. Some individuals also participate in these agreements because they are unable to purchase their own rice fields and want to work in the industry, while others do so to help those in need.